Penggunaan Aplikasi Busuu dalam Meningkatkan Kemampuan Menyimak Bahasa Jerman di SMA - Nursalam; Aztiana; Zahro, Diyan Fatimatuz (Nexus Publishing, 2024)
This study aims to determine the planning, implementation, and results of the application of the Busuu-App in improving the listening ability of class XI Language students of SMAN 7 Wajo. This research is a class action research consisting of 2 cycles, each of which contains planning, implementation, observation, and reflection. Research data consists of two types of data, namely qualitative data which is a description of the results of implementation and observation results during learning and quantitative data in the form of student listening ability test results presented in percentage form. The average listening score of class XI Language students in the first cycle was 59.28 and increased in second cycle to 75.71. The results of the study showed that the Busuu application can be applied during learning to improve students' listening skills.